2015
DOI: 10.1007/s00449-015-1385-8
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Aspergillus niger lipase on chitosan-coated magnetic nanoparticles using two covalent-binding methods

Abstract: Aspergillus niger lipase immobilization by covalent binding on chitosan-coated magnetic nanoparticles (CMNP), obtained by one-step co-precipitation, was studied. Hydroxyl and amino groups of support were activated using glycidol and glutaraldehyde, respectively. Fourier transform infrared spectrometry, high-resolution transmission electron microscopy and thermogravimetric analysis confirmed reaction of these coupling agents with the enzyme and achievement of a successful immobilization. The derivatives showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 21 publications
0
27
1
Order By: Relevance
“…The PES-ADS-lipase and PES-COV-lipase were more stable at 45 and 55°C, respectively ( Figure 7B and C). This result was better than that obtained by Osuna et al (2015), who obtained higher thermal stability at 30°C for A. niger lipase immobilised by covalent bonding on chitosan-coated magnetic nanoparticles. In general, the main factors responsible for the thermal stability of enzymes are protein hydrophobicity, the number of hydrogen and disulfide bonds, amino acid composition, and intermolecular interactions of the protein (Yu, Tan, Xiao, & Xu, 2012).…”
Section: Stability On Ph and Stability On Temperaturecontrasting
confidence: 70%
“…The PES-ADS-lipase and PES-COV-lipase were more stable at 45 and 55°C, respectively ( Figure 7B and C). This result was better than that obtained by Osuna et al (2015), who obtained higher thermal stability at 30°C for A. niger lipase immobilised by covalent bonding on chitosan-coated magnetic nanoparticles. In general, the main factors responsible for the thermal stability of enzymes are protein hydrophobicity, the number of hydrogen and disulfide bonds, amino acid composition, and intermolecular interactions of the protein (Yu, Tan, Xiao, & Xu, 2012).…”
Section: Stability On Ph and Stability On Temperaturecontrasting
confidence: 70%
“…An immobilization procedure for A. niger lipase by covalent binding on chitosan-coated magnetic nanoparticles was recently reported. 22 Immobilized derivatives retained above 80% of their initial activity after 15 hydrolytic cycles, and high storage stability during 50 days was observed. Also, lipase from Rhizomucor miehei and M. javanicus immobilized in microemulsion-based organogels maintained good enantioselectivities in the hydrolysis of ketoprofen vinyl ester and their activities increased 12.8-fold and 7.8-fold, respectively, compared with their free forms.…”
Section: Resultsmentioning
confidence: 92%
“…Enzyme immobilization on magnetite nanoparticles (MNPs) has attracted considerable attention recently for its unique advantages for the high specific surface area, low mass transfer resistance and convenient separation from the reaction mixture under a magnetic field (21,22). Many works have been reported that lipase could be immobilized on MNPs to enhance its stability and catalytic activity in enzymatic esterifications or resolutions (23)(24)(25)(26). However, improvement of lipase catalytic performance on MCRs by immobilization on MNPs has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%